Primary vertebral echinococcosis: A case of mistaken identity - Ashish Bansal,; Anjuna Reghunath,; Mahesh Kumar Mittal,; Reeta Kanaujia,; Nishu Raj, (Indian Journal of Case Reports, 2021)
Spinal hydatid is an uncommon entity that may cause paraplegia due to extensive cord compression. Often, the lesion may be misdiagnosed as spinal tuberculosis, especially in endemic countries. We report such a case of a young female with primary vertebral hydatid disease, who had been on antitubercular treatment for a long time due to misdiagnosis. We discuss the distinguishing diagnostic imaging features of this entity, which would beware radiologists of misdiagnosing this rare but serious condition.